A superelderly case of TAFRO syndrome treated effectively using corticosteroid hormones. Issue 4 (21st February 2018) - Shimada, Yoshitaka; Adachi, Mizuho; Kobayashi, Noritada; Okada, Takemichi; Yamazaki, Hitoshi; Nagaba, Yasushi; Yokomori, Hiroaki
Key Clinical Message: Peripheral lymphocyte subsets may be less time‐consuming and are a prognostic tool for managing thrombocytopenia, anasarca, myelofibrosis, renal dysfunction, and organomegaly (TAFRO) syndrome. Here, we report a superelderly case of plasma cell type TAFRO syndrome treated effectively using corticosteroid hormones. Abstract : Peripheral lymphocyte subsets may be less time‐consuming and are a prognostic tool for managing thrombocytopenia, anasarca, myelofibrosis, renal dysfunction, and organomegaly (TAFRO) syndrome. Here, we report a superelderly case of plasma cell type TAFRO syndrome treated effectively using corticosteroid hormones.